Prosperity gospel in Nigeria: A re-examination of the concept, impact, and evaluation - Folarin, George O. (African Journal of Biblical Studies, 2006)
The prosperity gospel is common in Nigeria. However, while many claim that the prosperity gospel is bad, they demonstrate remarkable ignorance of the meaning of the concept. This article therefore re-examines the concept of the prosperity gospel, its impact on non-Pentecostal evangelical denominations in Nigeria, and provides an assessment of the concept as it is presently used. A survey carried out in 2005 indicated that the prosperity gospel is the teaching that the solutions to people's problems of sin, sickness, poverty and demon oppression are in Jesus Christ. It also showed that charismatics are moving towards specialization in ministry. The Christ Apostolic Church and the Redeemed Christian Church of God major on healing, the Living Faith Church and the Church of God Mission International concentrate on financial breakthrough, and the Mountain of Fire and Miracles focuses on exorcism. No single denomination equally develops all the elements of the prosperity gospel and while every charismatic denomination or movement has provision for the spiritual growth of its members, the emphasis on this may not be adequate. A major problem with the prosperity gospel as presently practised in Nigeria is that it is not fully delivering on its promises. Its theology needs reformulating to make it conform more to the Scriptures and to incorporate the reality of Christian suffering. Notes, ref. [ASC Leiden abstract]